Qassim cement company: a case of ethical management - Khaliq, Ahmad; Fontaine, Rodrigue Ancelot Harvey; Kedah, Zulkarnain (Albukhary International University, 2021)
The development of the economy of Saudi Arabia outside of the petrol-related industries is vital to the future of Saudi Arabia. The Qassim Cement Company is one of the major companies in the field of building materials that contribute to strengthening the Saudi economy in general. This case explores the challenges of maintaining a high-level of competitiveness while remaining true to the values and practices embedded in the teachings of Islam. The Qassim Cement Company has sales of about SAR 800 million (about USD$ 200 million) and a workforce of about 650 people. It has a profit margin of around 34%. By comparison, the average profit margin in the cement industry varies between 10% and 20%. Yet at the same time, interviews with employees suggest that the company implements Islamic principles of management. This case raises an important philosophical question. Are management principles universal or should they be adapted to the local context.